2013
DOI: 10.2139/ssrn.2214818
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long-Term Effects of Environmental Tax Reform

Abstract: This paper examines the macroeconomic e¤ects of an environmental tax reform in a growing economy. A model of endogenous growth based on human capital accumulation is used to numerically simulate the growth e¤ects of di¤erent enironmental tax reforms and compute their impact on welfare in the short and the long-term. Our results suggest that the magnitude of these e¤ects depends on the type of tax reform. Thus, only environmental tax reform that aims to use the revenue from environmental tax to reduce wage tax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Ligthart (1998) found that any ETR will yield dividends for both the environment and the labor market, but only if revenue from green taxes is used to reduce the tax burden on the labor market. Oueslati (2013) further notes that the magnitude of the double dividend is a result of the type of ETR. Utilizing an endogenous growth model based on human capital accumulation to analyze the impact of different ETRs on welfare, the author concluded that only when green tax revenue is used to reduce income tax and increase spending on programs to promote depollution, welfare and economic growth improve in the long term.…”
Section: Theoretical Issues With Implementationmentioning
confidence: 99%
“…Ligthart (1998) found that any ETR will yield dividends for both the environment and the labor market, but only if revenue from green taxes is used to reduce the tax burden on the labor market. Oueslati (2013) further notes that the magnitude of the double dividend is a result of the type of ETR. Utilizing an endogenous growth model based on human capital accumulation to analyze the impact of different ETRs on welfare, the author concluded that only when green tax revenue is used to reduce income tax and increase spending on programs to promote depollution, welfare and economic growth improve in the long term.…”
Section: Theoretical Issues With Implementationmentioning
confidence: 99%
“…Likewise, increases in undesirable public investments-for example, in services that would have otherwise been provided by the private sector-are unlikely to raise welfare. By contrast, increasing public spending-for example, in road infrastructure, education, health, or social safety nets-could more than compensate for any welfare costs from a larger tax burden and increased prices for polluting goods (Oueslati 2013).…”
Section: Reason 3: Raising Domestic Resources To Fund Public Goodsmentioning
confidence: 99%
“…Šis klausimas aktualus visoms valstybėms -tiek toms, kurios jau įgyvendinusios ekologinių mokesčių reformą, tiek ir toms, kurios ją rengiasi įgyvendinti (Heine, 2012). W. Oueslati (2013) tyrimai rodo, kad Švedijoje, Suomijoje, Vokietijoje, Nyderlanduose, Jungtinėje Karalystėje, Italijoje ir Norvegijoje, įgyvendinusioms ekologinių mokesčių reformą, pajamų iš šių mokesčių dalis bendroje surinktų mokesčių sumoje padidėjo 2 proc., o jų dalis BVP kai kuriose valstybėse išaugo net 9 proc.…”
Section: įVadasunclassified